How "should" we write guideline recommendations? Interpretation of deontic terminology in clinical practice guidelines: survey of the health services community. Issue 6 (10th August 2010) - Lomotan, E A; Michel, G; Lin, Z; Shiffman, R N
Abstract : Objective: To describe the level of obligation conveyed by deontic terms (words such as "should", "may", "must" and "is indicated") commonly found in clinical practice guidelines. Design: Cross-sectional electronic survey. Setting: A clinical scenario was developed by the researchers, and recommendations containing 12 deontic terms and phrases were presented to the participants. Participants: All 1332 registrants of the 2008 annual conference of the US Agency for Healthcare Research and Quality. Main outcome measures: Participants indicated the level of obligation they believed guideline authors intended by using a slider mechanism ranging from "No obligation" (leftmost position recorded as 0) to "Full obligation" (rightmost position recorded as 100.) Results: 445/1332 registrants (36%) submitted the on-line survey; 254/445 (57%) reported that they have experience in developing clinical practice guidelines; 133/445 (30%) indicated that they provide healthcare. "Must" conveyed the highest level of obligation (median=100) and least amount of variability (interquartile range=5.) "May" (median=37) and "may consider" (median=33) conveyed the lowest levels of obligation. All other terms conveyed intermediate levels of obligation characterised by wide and overlapping interquartile ranges. Conclusions: Members of the health services community believe guideline authors intend variable levels of obligation when using different deontic terms within practice recommendations. Ranking of a subset of terms by intended level of obligation is possible. Matching deontic terminology to the intended recommendation strength can help standardise the use of deontic terminology by guideline developers.